The Effect of Hexagon Fraud Theory in Detecting Financial Statement Fraud - Adhania, Safira; Holiawati, Holiawati; Nofryanti, Nofryanti (International Journal of Digital Marketing Science, 2024)
Purpose – The purpose of this research is to determine the effect of hexagon fraud theory in detecting financial statement fraud. Methodology/approach – This research uses a sample of insurance companies listed on the Indonesia Stock Exchange during the 2018-2022 period. The sampling technique used in this research was a side purposive technique, the samples obtained were 15 insurance companies or 75 data observations. The analytical method used is logistic analysis using SPSS.24. Findings – Based on the results of this research, it shows that External Pressure has a significant effect on Financial Report Fraud, Political Connection has a significant effect on Financial Report Fraud, Nature of Industry has a significant effect on Financial Report Fraud, and Effective Monitoring has a significant effect on Financial Report Fraud, while Financial Stability does not have a significant effect on Financial Report Fraud, Financial Target does not have a significant effect on Financial Statement Fraud, Personal Financial Need does not have a significant effect on Financial Report Fraud, Capability does not have a significant effect on Financial Report Fraud, Rationalization does not have a significant effect on Report Fraud Finance, Arrogance does not have a significant effect on Financial Statement Fraud.